Mutations in C12orf62, a Factor that Couples COX I Synthesis with Cytochrome c Oxidase Assembly, Cause Fatal Neonatal Lactic Acidosis - Weraarpachai, Woranontee; Sasarman, Florin; Nishimura, Tamiko; Antonicka, Hana; Auré, Karine; Rötig, Agnès; Lombès, Anne; Shoubridge, Eric A. (American journal of human genetics, 2012)
We investigated a family in which the index subject presented with severe congenital lactic acidosis and dysmorphic features associated with a cytochrome c oxidase (COX)-assembly defect and a specific decrease in the synthesis of COX I, the subunit that nucleates COX assembly. Using a combination of microcell-mediated chromosome transfer, homozygosity mapping, and transcript profiling, we mapped the gene defect to chromosome 12 and identified a homozygous missense mutation (c.88G>A) in C12orf62. C12orf62 was not detectable by immunoblot analysis in subject fibroblasts, and retroviral expression of the wild-type C12orf62 cDNA rescued the biochemical phenotype. Furthermore, siRNA-mediated knockdown of C12orf 62 recapitulated the biochemical defect in control cells and exacerbated it in subject cells. C12orf62 is apparently restricted to the vertebrate lineage. It codes for a very small (6 kDa), uncharacterized, single-transmembrane protein that localizes to mitochondria and elutes in a complex of ∼110 kDa by gel filtration. COX I, II, and IV coimmunoprecipated with an epitope-tagged version of C12orf62, and 2D blue-native-polyacrylamide-gel-electrophoresis analysis of newly synthesized mitochondrial COX subunits in subject fibroblasts showed that COX assembly was impaired and that the nascent enzyme complex was unstable. We conclude that C12orf62 is required for coordination of the early steps of COX assembly with the synthesis of COX I.